2005
DOI: 10.1097/01.fpc.0000174788.69991.6b
|View full text |Cite
|
Sign up to set email alerts
|

Thiopurine S-methyltransferase pharmacogenetics: variant allele functional and comparative genomics

Abstract: Thiopurine S-methyltransferase (TPMT) catalyses the S-methylation of thiopurine drugs. Genetic polymorphisms for TPMT are a major factor responsible for large individual variations in thiopurine toxicity and therapeutic effect. The present study investigated the functional effects of human TPMT variant alleles that alter the encoded amino acid sequence of the enzyme, TPMT*2, *3A, *3B, *3C and *5 to *13. After expression in COS-1 cells and correction for transfection efficiency, allozymes encoded by these allel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
123
0
7

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(138 citation statements)
references
References 60 publications
8
123
0
7
Order By: Relevance
“…This phenomenon has also been observed for many other common genetic polymorphisms that alter only a single amino acid (Freimuth et al, 2001;Thomae et al, 2002;Adjei et al, 2003;Thomae et al, 2003;Weinshilboum and Wang, 2004a;Ji et al, 2005). Of the allozymes studied by Salavaggione et al (2005), TPMT*3A, *3B, *3C and *2 displayed the most striking effects. This phenomenon was first observed a decade ago when TPMT*3A, *3B and *3C were initially described (Szumlanski et al, 1996).…”
Section: Tpmt: Functional Genomics and Molecular Mechanismsmentioning
confidence: 56%
See 1 more Smart Citation
“…This phenomenon has also been observed for many other common genetic polymorphisms that alter only a single amino acid (Freimuth et al, 2001;Thomae et al, 2002;Adjei et al, 2003;Thomae et al, 2003;Weinshilboum and Wang, 2004a;Ji et al, 2005). Of the allozymes studied by Salavaggione et al (2005), TPMT*3A, *3B, *3C and *2 displayed the most striking effects. This phenomenon was first observed a decade ago when TPMT*3A, *3B and *3C were initially described (Szumlanski et al, 1996).…”
Section: Tpmt: Functional Genomics and Molecular Mechanismsmentioning
confidence: 56%
“…The reason why altering only two amino acids out of 245 results in such a striking phenotype will be addressed subsequently. TPMT*3C and the first variant allele identified, TPMT*2, do not result in such dramatic decreases in levels of enzyme protein as do *3A and *3B, but they are also associated with significant decreases in quantity of TPMT protein (Tai et al, , 1999Wang et al, 2003;Salavaggione et al, 2005). On the basis of population studies, *3A and *3C are the predominant variant alleles, with *2 contributing to a lesser extent.…”
Section: Tpmt Genetic Polymorphism: Discovery and Clinical Significancementioning
confidence: 99%
“…The TPMT gene is highly polymorphic; more than 25 variants have been identified. Four alleles (TPMT*2, *3A, *3B, and *3C) account for approximately 95% of inherited TPMT deficiency [109][110][111] . The wild-type allele, TPMT*1, encodes the fully active enzyme, and TPMT*2, TPMT*3A and TPMT*3C are the most prevalent genotypes in Caucasians, together accounting for 80% to 95% of the polymorphic alleles that lead to a significant reduction in enzyme activity due to enhanced rates of proteolysis of the mutant proteins [112] .…”
Section: Azathioprinementioning
confidence: 99%
“…TPMT is a cytosolic methylating enzyme whose physiological role remains unclear despite extensive investigation. It is reported that a reduction in TPMT activity, caused by genetic polymorphisms results in severe and hematological toxicity in patients treated with standard doses of thiopurines [108,109] . Approximately 0.3% of individuals in a general population had low levels of TPMT activity, with approximately 10% of individuals expressing intermediate levels [108] .…”
Section: Azathioprinementioning
confidence: 99%
“…In African populations, *3C and *2 are also common. All of these variants demonstrate reduced in vitro enzyme activity 49 . Around 10% of the population Copyright Ó 2016 Wolters Kluwer Health, Inc.…”
Section: Tpmt Functional Variants (A)mentioning
confidence: 99%